(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: 75% of Indonesian women have ever used femininity liquid cleaning soap that was In Indonesia, 55% of productive woman had tormented by dysmenorrhoea, with pravelence ranging from 45-95% in productive age (Proverawati and Misaroh, 2009). The womenhad dysmenorrhoea more bad in achievement than the women had not dysmenorrhoea. The usage of warm compresses were a way to eliminated or decreaced the pain without side effetcts. Objective: Knowing the knowledge of young women in the handling of primary dysmenorrhoea with warm compresses in especially include menstruation comperhension, the cause of dysmenorrhoea, dysmenorrhoea indication, and handling of primary dysmenorrhoea. Method: Descriptive as the kind of research with survey in approach. The research population amounted to 50 respondents was all young women in Class XI IPA of 1 Mlati Senior High School, Sleman,. The sampling technique of sample. The tool of collection used questionnaires. The data analysis used univariant and described in precentage. Results: The young women knowledge about handling of primary dysmenorrhoea with warm compresses were mostly good category (76%), that includes about menstruatuon comperhension were mostly good category (100%), dysmenorrhoea comperhension were mostly good category (70%), the cause of dysmenorrhoea were mostly less category (64%), dysmenorrhoea indication were nostly less category (60%), handling of primary dysmenorrhoea were mostly good category (76%). Conclusion: The young women knowledge about handling of primary dysmenorrhoea with warm compresses in Class XI IPA in 1 Mlati Senior High School, Sleman, Yogyakarta were good at 76%. Keywords: The knowledge, young women, primary dysmenorrhoea, warm compresses.